2008
DOI: 10.1182/blood-2007-01-068957
|View full text |Cite
|
Sign up to set email alerts
|

The factor VIII C1 domain contributes to platelet binding

Abstract: Activated factor VIII (FVIIIa) forms a procoagulant complex with factor IXa on negatively charged membranes, including activated platelet surfaces. Membrane attachment involves the FVIII C2 domain; involvement of the adjacent C1 domain has not been established. Binding of recombinant FVIII C1C2 and C2 proteins to platelets was detected by flow cytometry using (1) anti-C2 monoclonal antibody ESH8 followed by a phycoerythrinlabeled secondary antibody; (2) biotinylated C1C2 detected by phycoerythrinlabeled strept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 46 publications
3
40
1
1
Order By: Relevance
“…The positioning of the C1 domain relative to the C2 domain supports previous data indicating that the C1 domain contributes to membrane association and the C2 domain is not essential for function. [29][30][31] Lastly, the x-ray crystal structure of the C2 domain/3E6/G99 complex is remarkably similar to the previously modeled ternary complex from low-resolution SAXS data ( Figure 1B). 41 These structural findings suggest that using rapid, low-resolution techniques such as SAXS may be effective tools for characterizing other antibody epitopes for fVIII inhibitor antibodies as well as other antigen/antibody interactions.…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…The positioning of the C1 domain relative to the C2 domain supports previous data indicating that the C1 domain contributes to membrane association and the C2 domain is not essential for function. [29][30][31] Lastly, the x-ray crystal structure of the C2 domain/3E6/G99 complex is remarkably similar to the previously modeled ternary complex from low-resolution SAXS data ( Figure 1B). 41 These structural findings suggest that using rapid, low-resolution techniques such as SAXS may be effective tools for characterizing other antibody epitopes for fVIII inhibitor antibodies as well as other antigen/antibody interactions.…”
mentioning
confidence: 48%
“…22 In addition to interactions with phospholipid (PL) and VWF, there are previous reports that suggest the C2 domain contributes to the binding of thrombin and factor Xa to full-length fVIII, potentially acting as a docking module that may stabilize and promote the proteolytic activity of factor Xa/thrombin cleavages elsewhere in fVIII during activation. [26][27][28] Recent studies also suggest that the C1 domain contributes to binding both VWF and PS, 29,30 and deletion studies of the C2 domain indicate that it is not essential for PL membrane binding, factor IXa binding, or clotting activity. 31 The C2 domain of fVIII is a major antigenic determinant for recognition by inhibitor antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Additional work will also be required to indicate whether the C1 domain [15][16][17] or A3 domain 41 also contribute to binding the fibrin-dependent platelet sites.…”
Section: Discussionmentioning
confidence: 99%
“…14 The C1 and C2 domains mediate membrane binding. [15][16][17][18][19] The fVIII C domains share similar sequence and structure with the C domains of factor V [20][21][22] and lactadherin, 23 a milk fat globule membrane protein. Like fVIII, both factor V and lactadherin bind to PS-containing membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have described the involvement of the C1 domain in binding to VWF and phospholipid membranes. 20,21 Recently negativestain electron microscopy and hydrogen-deuterium exchange mass spectrometry (HDX MS) studies have revealed that VWF primarily interacts with the C1 domain of fVIII. 22,23 VWF binding protects fVIII from endocytosis 24 and the human-derived anti-C1 domain antibody KM33 inhibits fVIII uptake by human monocyte-derived dendritic cells (MDDCs).…”
Section: Introductionmentioning
confidence: 99%